Goodbaby : how a Chinese underdog became a world leader through open innovation - Chesbrough, Henry, (SAGE Business cases., 2021)
This case shows how Goodbaby, a Chinese maker of juvenile products like strollers, carseats, and cribs, rose from nothing to global leadership. While there are several important moments in this journey, a commitment to open innovation characterizes each transition on the path to No. 1.The case describes the origins of Goodbaby, and its rise to industry leadership. Founded by a former school teacher, the company made several big investments to grow its capabilities, and pioneered an Inside-out open innovation strategy that allowed it to offer its own produces under its own brands, and in tandem offer its products to customers under their brands.The key focus in this case is the decision to invest significantly greater resources in R&D to build strong product differentiation and improved performance for Goodbaby's products. At the same time, the company adopted business models of OEM, ODM and OPM collaboration with customers who often were also competitors. Issues of access, pricing, and prioritization of competitors vs. inhouse products had to be created, to make this policy a reality.